Early-Life Antibiotic Exposure and Childhood Asthma Trajectories: A National Population-Based Birth Cohort - Lu, Yankun; Wang, Yichao; Wang, Jing; Lowe, Adrian J; Grzeskowiak, Luke E; Hu, Yanhong J (My University, 2023)
Introduction: Early-life antibiotic exposure is common and impacts the development of the child’s microbiome and immune system. Information on the impacts of early-life antibiotics exposure on childhood asthma is lacking. Methods: This study examined associations between early-life (0–24 months) antibiotics exposure with childhood (6–15 years) asthma trajectories through the Australian Longitudinal Study of Australian Children (LSAC) and their linked data from the Pharmaceutical Benefits Scheme. Asthma phenotypes were derived by group-based trajectory modeling. Results: Of 5107 LSAC participants, 4318 were included in the final analyses (84.6% retention). Four asthma phenotypes were identified: Always-low-risk (79.0%), early-resolving asthma (7.1%), early-persistent asthma (7.9%), and late-onset asthma (6.0%). Any early-life antibiotic exposure increased risk 2.3-fold (95% CI: 1.47–3.67; p < 0.001) for early-persistent asthma among all children. In subgroup analyses, early-persistent asthma risk increased by 2.7-fold with any second-generation cephalosporin exposure, and by 2-fold with any β-lactam other than cephalosporin or macrolide exposure. Conclusion: We concluded that early-life antibiotic exposure is associated with an increased risk of early-persistent childhood asthma. This reinforces scrutiny of early-life antibiotic use, particularly for common viral infections where no antibiotics are required.
Antibiotics -MDPI
Keywords: antibiotic; asthma; birth cohort; childhood; early-life; trajectory; Childhood and child development; Health and wellbeing